"I be da reel gansta"—A Finnish footballer's Twitter writing and metapragmatic evaluations of authenticity. (June 2015) - Kytölä, Samu; Westinen, Elina
Abstract: This article explores the ways in which 'gangsta' English features are deployed, evaluated and adopted in two types of social media, the web forum and Twitter, within the domains of hip hop culture and football (soccer) culture, from the dual perspective of authenticity and normativity. Empirically, we aim to break new ground by investigating the intricate interconnections between two social media formats and combining two highly popular but previously seldom connected cultural forms—football and hip hop. Our theoretical aim is to contribute to the current debate on authenticity, normativity, popular culture and social media, and the complex ways in which they are connected. We focus, first, on the Twitter writing of the Finnish footballer Mikael Forssell, specifically his uses of non-Standard English and references to hip hop culture and rap music, and second, on the ways in which Forssell's stylized writing elicits normatively oriented metapragmatic commentaries, i.e., meta-level discussion, on a major Finnish football discussion forum. Of particular interest here is the emically emerging category of 'gangsta' English and its perceived (in)authenticity—when used by Forssell and two other ('White') middle-class Finnish footballers. Drawing on the frameworks of authenticity and sociolinguistic superdiversity, we foreground the tension between purist normativity and playful appropriation online. Our discussion highlights the unpredictability of the connections between language use, (popular) cultural forms, ethnicity, country of origin, and the complexity of mediation across online and offline sites of social action. Highlights: Use of 'gangsta' English features in Twitter and a Finnish football web forum. Metapragmatic normative evaluations of the authenticity of a footballer's 'gangsta' writing. Appropriation of a negatively evaluated style of writing for jocular in-group purposes. Intricate interconnections between polycentric hip hop and football cultures. Tension between language use, country of origin, ethnicity, popular culture and digital mediation.